Group 5 drugs for multidrug-resistant tuberculosis: individual patient data meta-analysis - Fox, Greg J; Benedetti, Andrea; Cox, Helen; Koh, Won-Jung; Viiklepp, Piret; Ahuja, Shama; Pasvol, Geoffrey; Menzies, Dick (The European respiratory journal, 2017)
The role of so-called "group 5" second-line drugs as a part of antibiotic therapy for multidrug-resistant tuberculosis (MDR-TB) is widely debated. We performed an individual patient data meta-analysis to evaluate the effectiveness of several group 5 drugs including amoxicillin/clavulanic acid, thioacetazone, the macrolide antibiotics, linezolid, clofazimine and terizidone for treatment of patients with MDR-TB.Detailed individual patient data were obtained from 31 published cohort studies of MDR-TB therapy. Pooled treatment outcomes for each group 5 drug were calculated using a random effects meta-analysis. Primary analyses compared treatment success to a combined outcome of failure, relapse or death.Among 9282 included patients, 2191 received at least one group 5 drug. We found no improvement in treatment success among patients taking clofazimine, amoxicillin/clavulanic acid or macrolide antibiotics, despite applying a number of statistical approaches to control confounding. Thioacetazone was associated with increased treatment success (OR 2.6, 95% CI 1.1-6.1) when matched controls were selected from studies in which the group 5 drugs were not used at all, although this result was heavily influenced by a single study.The development of more effective antibiotics to treat drug-resistant TB remains an urgent priority.